2022
DOI: 10.3390/medicina58050654
|View full text |Cite
|
Sign up to set email alerts
|

Water Dynamics in Cancer Cells: Lessons from Quasielastic Neutron Scattering

Abstract: The severity of the cancer statistics around the globe and the complexity involving the behavior of cancer cells inevitably calls for contributions from multidisciplinary areas of research. As such, materials science became a powerful asset to support biological research in comprehending the macro and microscopic behavior of cancer cells and untangling factors that may contribute to their progression or remission. The contributions of cellular water dynamics in this process have always been debated and, in rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The new generation spallation source and reactor backscattering spectrometers have already opened new doors in recent years for high-resolution neutron spectroscopy. For instance, in life sciences it is now possible to unravel the complex dynamics of such water-dependent complex morphologies using neutron spectroscopy [30]. Nevertheless, structural information from QENS experiments on complex systems depends on the observation-time (Δt) H , which is defined by the spectrometer setting and its resolution function [31].…”
Section: Water Dynamics In Biosystems and The Miracles Backscattering...mentioning
confidence: 99%
See 1 more Smart Citation
“…The new generation spallation source and reactor backscattering spectrometers have already opened new doors in recent years for high-resolution neutron spectroscopy. For instance, in life sciences it is now possible to unravel the complex dynamics of such water-dependent complex morphologies using neutron spectroscopy [30]. Nevertheless, structural information from QENS experiments on complex systems depends on the observation-time (Δt) H , which is defined by the spectrometer setting and its resolution function [31].…”
Section: Water Dynamics In Biosystems and The Miracles Backscattering...mentioning
confidence: 99%
“…Incoherent neutron scattering, on the other hand can provide unique and unambiguous access to the self-diffusion coefficient, but the investigations of the diffusion dynamics of living systems using neutron spectrometers has been severely hindered until recently because of the limited flux provided by the instruments. However, the advent of such research has just begun due to the development of the third-generation neutron backscattering instruments [4,30,[46][47][48], but continued growth will depend on the highest-flux and flexibility provided by the backscattering spectrometer MIRACLES. Additionally, neutron scattering offers the unique capability of performing experiments in various extreme environments, such as humidity [49], pressure [50], electrical stimuli [51], pump probe [52].…”
Section: Case 1: Short Time Dynamics Of Water In Living Systemsmentioning
confidence: 99%
“…Recently reviewed [ 12 , 31 ] neutron spectroscopy studies of cancer cells represent a distinct line of research. In a pioneering study [ 32 ], it was reported that exposure of human metastatic breast cancer cells to an anticancer drug, cisplatin, induced distinct responses in the non-hydrating cytoplasmic and hydrating water molecules, which exhibited, respectively, suppressed and enhanced diffusion dynamics.…”
Section: Incoherent Neutron Spectroscopy: Cellular Levelmentioning
confidence: 99%
“…Although much less developed compared to measurements of model biosystems, inelastic neutron scattering from real-life biological samples holds promise for a better understanding of biological complexity. We do not intend to concentrate on the details of the incoherent neutron spectroscopy methods, as they have been discussed in several books and some very recent review articles [ 12 ]. Instead, we focus on interpretation of the information provided by neutron spectroscopic measurements of complex biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence for anomalous diffusion of water in biological tissues, measured by nuclear magnetic resonance (NMR) has been extensively documented ( Köpf et al, 1996 ), leading to the development of diffusion-weighted magnetic resonance imaging (DW-MRI), applied to cancer diagnosis and follow-up after treatment ( Patterson et al, 2008 ). Interestingly, the role played by another technique, quasielastic neutron scattering (QENS), provided additional value in understanding the role played by water molecules in tumors before and after treatment with chemotherapy drugs ( Martins et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%